A Novel, Automated Text-Messaging System Is Effective in Patients Undergoing Total Joint Arthroplasty. (16th January 2019) - Campbell, Kevin J.; Louie, Philip K.; Bohl, Daniel D.; Edmiston, Tori; Mikhail, Christopher; Li, Jefferson; Khorsand, Derek A.; Levine, Brett R.; Gerlinger, Tad L.
Abstract : Background: Digital patient engagement platforms are designed to improve the efficacy of the perioperative surgical home, but the currently available solutions have shown low patient and provider adoption. The purpose of this study was to evaluate the effectiveness of a text-messaging (Short Message Service [SMS]) bot with respect to patient engagement following joint replacement procedures in a randomized clinical trial. Methods: One hundred and fifty-nine patients (83 patients in the control group and 76 patients in the intervention group) were enrolled in a randomized controlled trial comparing the effectiveness of an SMS bot (intervention group) with the traditional perioperative education process (control group) in patients undergoing primary total knee or hip arthroplasty. There were no significant differences in the demographic characteristics between the 2 groups. The primary outcome of time participating in home-based exercises and the secondary outcomes of knee range of motion, the use of narcotics, visual analog scale (VAS) mood score, telephone calls to the office, patient satisfaction, and visits to the emergency department were measured and were compared between the 2 groups. Continuous outcomes were analyzed using linear regression, and categorical outcomes were analyzed using the Pearson chi-square test. Results: Patients in the intervention group exercised for 8.6 minutes more per day: a mean time (and standard deviation) of 46.4 ± 17.4 minutes compared with 37.7 ± 16.3 minutes for the control group (p < 0.001). The intervention group had an improved mood (mean VAS, 7.5 ± 1.8 points compared with 6.5 ± 1.7 points for the control group; p < 0.001), stopped their narcotic medications 10 days sooner (mean time, 22.5 ± 13.4 days compared with 32.4 ± 11.8 days for the control group; p < 0.001), placed fewer telephone calls to the surgeon's office (mean calls, 0.6 ± 0.8 compared with 2.6 ± 3.4 for the control group; p < 0.001), and had greater knee range of motion 3 weeks after the surgical procedure (mean flexion, 101.2° ± 11.2° compared with 93.8° ± 14.5° for the control group; p = 0.008), but had an equal range of motion at 6 weeks. There was a trend toward fewer visits to the emergency department in the intervention group, but this comparison lacked statistical power. Conclusions: An SMS bot can improve clinical outcomes and increase patient engagement in the early postoperative period in patients undergoing hip or knee arthroplasty. Level of Evidence: TherapeuticLevel I . See Instructions for Authors for a complete description of levels of evidence.